ANALYSING THE TYPES OF ENGLISH LEARNING DIFFICULTIES OF THAI STUDENTS IN INDONESIA - Rahayuningmas , Dyan; Aniuranti, Asfi; Tsani, M.Happy Nur (Economics, Social, and Humanities Journal (Esochum), 2024)
This research aimed to find out students’ difficulties in learning English. The method employed was a case study. The data was collected through interviews. The participants of this study were seven Thai students of the English Language Teaching Study Program of Universitas Nahdlatul Ulama Purwokerto. The results revealed that in learning listening skills, the students faced difficult accents and a lack of vocabulary. Next, in reading skill, the students encountered two types of learning challenges called lack of vocabulary and difficult to comprehend the whole text. In learning speaking skills, the students had four types of difficulties namely unconfident and nervous, lack of vocabulary, difficulty with accent, and fluency. In mastering writing, Thai students had several problems called lack of vocabulary and difficulty understanding the grammar rules. Furthermore, the pupils had certain challenges when learning subskills. The pupils encountered the difficulty of remembering and comprehending the meaning when learning new words. Secondly, the students believed that understanding English grammar was difficult when they were studying it. Finally, the students faced challenges with the complex pronunciation system, Thai accent effect, and suprasegmental feature (stress) when learning pronunciation. In short, Thai students who learned English as a foreign language in a foreign country faced several types of learning difficulties.